Identifikasi Peningkatan Strength Factor Dengan Metode Q-System Pada Terowongan Tambang Bawah Tanah Daerah Perambahan, Kota Sawahlunto, Sumatera Barat - Pebby Putra Juenda; Harnani Harnani; Budhi Setiawan (MINERAL, 2022)
Underground mining activities (Undergound Mining) at PT Allied Indo Coal Jaya Encroachment area, Sawahlunto City has the risk of subsidence due to reduced soil carrying capacity due to excavation of underground mine openings. The excavation of underground mine openings will result in disruption of the stability of the area such as roof collapse, rib spalling, and floor heave. This research was conducted in 2 research locations, namely Tunnel 6 Seam B and Tunnel 3 Seam C which aims to determine the recommendation of a buffer system in underground mine openings (Tunnel) by analyzing the geomechanical value of rocks using the Rock Tunnelling Quality Index (Q-System) method. ) so that the Strength Factor value increases. Data collection methods were carried out by field observation and laboratory testing, while data processing used Phase 8.0 software with Mohr-Coulomb failure criteria. The results of calculations and data processing showed that the Strength Factor value in Tunnel 6 Seam B was 1,04 (relatively stable) and Tunnel 3 Seam C was 0,84 (unstable). These results indicate that Tunnel 6 Seam B and Tunnel 3 Seam C must be supported by a buffer system. After the buffering system was carried out the Strength Factor value of Tunnel 6 Seam B increased to 1,59 (stable) and Tunnel 3 Seam C increased to 1,63 (stable).